LIFE-CYCLE HYPOTHESIS OF HYBRID SUKUK - Moonda, Luthvia (Jurisdictie: Jurnal Hukum dan Syariah, 2019)
The development of financial system recently has been contributing to the economic growth of the nation. Its vital role helps many financial institutions to advance their financial services, particularly in investment systems such as Sukuk. As seen in recent years, the involvement of Sukuk in many industries ranging from sovereigns to corporates for both Muslim and non-Muslim world companies. Although its popularity increases, it seems to be widely accepted that the insufficient structures of Sukuk become a big challenge to serve the public needs to be in compliance with Shari’ah principles. In an attempt to fulfil many financial companies in issuing Sukuk and the needs of the Muslim world, this study aims to provide the new structure of Sukuk. The study proposes a design of securitization by combining two contracts of Sukuk into one Sukuk structure. The constructed idea will use a model of life cycle hypothesis to support the Sukuk issuing companies in maintaining their incomes. It also explains the cycle cash flow and asset movement as well as the calculation of Net Present Value (NPV) of the project.